Clinical Effect of Minimally Invasive Microendoscopic‐Assisted Transforaminal Lumbar Interbody Fusion for Single‐Level Lumbar Disc Herniation. Issue 12 (27th October 2022) - Chen, Gang; Li, Long Biao; Shangguan, Zhitao; Wang, Zhenyu; Liu, Wenge; Li, Jiandong
Abstract : Objective: This retrospective study aimed to compare the clinical and radiological outcomes of transforaminal lumbar interbody fusion (TLIF) through the Wiltse approach (W‐TLIF) vs minimally invasive microendoscopy‐assisted transforaminal lumbar interbody fusion (ME‐TLIF) in single‐segment lumbar disc herniation (LDH). Methods: A retrospective study was conducted to study the differences in specific clinical outcomes between single‐segment LDH patients receiving W‐TLIF and ME‐TLIF. Single‐segment LDH patients admitted to the Fujian Medical University Union Hospital from March 2015 to June 2018 were included. All the participants were divided into the ME‐TLIF group or the W‐TLIF group according to their TLIF surgery types. Demographic characteristics, the visual analog score (VAS), Oswestry Disability Index (ODI), Japanese Orthopaedic Association (JOA) scale, blood loss volume, postoperative drainage, ambulated time, initial postoperative back pain, hospitalization duration, expenses, and improvement rates of patients in the two groups were collected for analysis. Radiographic fusion was ultimately assessed via the Bridwell interbody fusion grading system. All selected patients with TLIF were followed up for 1 year. Results: Fifty‐seven patients were selected, with 26 in the ME‐TLIF group and 31 in the W‐TLIF group, both of whom were followed up for 1 year. The mean age of the included patients was 53.75 ± 9.313 years, and the sex ratio was indiscrimination. There was no significant difference in demographic data or operating time between the two groups prior to surgery. The blood loss volume (ME‐TLIF: 228.5 vs W‐TLIF: 681.3), postoperative drainage (ME‐TLIF:82.1 ± 23.5 vs W‐TLIF: 345.8 ± 65.2), initial postoperative back pain (ME‐TLIF: VAS_3 days: 1.96 ± 0.60 VAS_7 days: 1.73 ± 0.53, W‐TLIF: VAS_3 days: 2.48 ± 0.51 VAS_7 days: 1.87 ± 0.43), and hospitalization duration (ME‐TLIF: 9.04 vs. W‐TLIF: 11.29) were all significantly lower in the ME‐TILF group ( p < 0.05). However, there were no statistical differences between the two groups in VAS, ODI, and JOA at 1 month, 3 months, 6 months, and 1 year postoperatively ( p > 0.05). The fusion rates of the two groups showed no notable difference ( p > 0.05), while the X‐ray exposure time in the ME‐TLIF group was significantly longer than in the W‐TLIF group ( p < 0.05). Conclusions: ME‐TLIF surgery was an effective and satisfactory surgical technique to manage LDH. Although ME‐TLIF increased the operation time and intraoperative fluoroscopic irradiation volume, it could effectively relieve low back pain from early postoperative onset and promote early postoperative recovery compared with W‐TLIF. Abstract : Minimally invasive surgical instruments for the MET‐Rx Microsightoscopy System (Medtronic) and a brief description of surgery procedure.